2022
DOI: 10.2147/ijgm.s369306
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ Knowledge and Practices Regarding Asthma: A Cross-Sectional Study in Saudi Arabia

Abstract: Objective This study aimed to explore the characteristics of knowledge and practice of physicians towards asthma in Saudi Arabia. Methods An online cross-sectional study was conducted in Saudi Arabia between 28 August and 10 November 2021. Convenience sampling technique was applied in this study through social media websites. Previously developed 10-items questionnaire was used to assess the knowledge about asthma among the participating physicians. Descriptive statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A recent study in Saudi Arabia found that almost half of the research participants understood the triggers connected to asthma. 21 Along with the study's findings, more than half of the participants thought diagnostic instruments such as spirometer, chest radiography, peak flow meter, and arterial blood gases were essential for diagnosing asthma. The result of Adeniyi et al (2017) in South-West Nigeria found that the percentage of physicians using diagnostic tools peak flow meter (97%), spirometer (95%), and chest radiography (61%) to diagnose asthma.…”
Section: Dovepressmentioning
confidence: 84%
See 2 more Smart Citations
“…A recent study in Saudi Arabia found that almost half of the research participants understood the triggers connected to asthma. 21 Along with the study's findings, more than half of the participants thought diagnostic instruments such as spirometer, chest radiography, peak flow meter, and arterial blood gases were essential for diagnosing asthma. The result of Adeniyi et al (2017) in South-West Nigeria found that the percentage of physicians using diagnostic tools peak flow meter (97%), spirometer (95%), and chest radiography (61%) to diagnose asthma.…”
Section: Dovepressmentioning
confidence: 84%
“…A further finding revealed that, on average, 63.7% ± 5.7% of physicians confirmed managing asthma according to GINA recommendations. 21 Roman-Rodriguez et al also stated that only a low proportion (26%) of physicians followed the asthma guidelines in a prior study conducted in Spain. 31 Amorha et al also reported that only 11.2% of community pharmacists successfully implemented the GINA report.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation